Parallel diffusion of energetic particles interacting with noisy reduced MHD turbulence. Issue 4 (13th January 2016) - Reimer, A.; Shalchi, A.
Abstract: We investigate analytically parallel diffusion in noisy reduced magnetohydrodynamic (NRMHD) turbulence. We employ different theories such as quasi-linear theory, second-order quasi-linear theory, and the weakly non-linear theory to compute the parallel diffusion coefficient. Our analytical findings are compared with test-particle simulations performed previously. We demonstrate systematically that quasi-linear theory does not work for the turbulence model considered here because it provides an infinite parallel diffusion coefficient. The second-order theory, on the other hand, provides a finite parallel mean free path which is, however, too large. Only by using the weakly non-linear theory we can reproduce the simulations and, thus, we conclude that resonance broadening due to perpendicular diffusion is an important effect if it comes to particle transport along the mean field in NRMHD turbulence.